Brain Protection pada Traumatik Brain Injury - Sudadi (This journal is published by the Department of Anesthesiology and Intensive Therapy of Faculty of Medicine, Public Health and Nursing, in collaboration with the Indonesian Society of Anesthesiology and Intensive Therapy , Yogyakarta Special Region Br, 2017)
Trauma is the leading cause of death in children and people under 45 years old, and brain trauma is theleading cause of death in 25% of cases. Brain trauma can be classified as both primary and secondary injury.Primary brain injury is a direct result on the head causing both anatomical and physiological damage.Secondary brain injury is the result of hypotension, hypoxia, acidosis, edema, or other advanced factors thatcause damage to brain tissue. Brain protection as prevention and improvement of neuronal damage causedby abnormalities of cerebral metabolism, histopathological or neurological functioning that occurs afterhypoxia or ischemic conditions. The key elements in brain protection that must be achieved are loweringoxygen demand, increasing oxygen supply and halting intracellular pathological processes.